The prairie winnows out its own : the West River Country of South Dakota in the years of depression and dust - Nelson, Paula, 1951- (Book collections on Project MUSE., 1996)
Between 1900 and 1915, in the last great land rush, over one hundred thousand homesteaders flooded into the west river country of South Dakota, a land noted for its aridity and unpredictable weather, its treelessness, and its endless sky. The settlers of "the last, best west" weathered their first crisis in the severe drought of 1910-1911, which winnowed out many of the speculators and faint of heart; they abandoned their founding hopes of quick success and substituted a new ethos of "next year country"--While this year was hard, next year would be better